Research of the gain of silicon photomultipliers in a temperature chamber at various voltages - Moskalenko, Victoriya D. (Двадцатая Всероссийская конференция студенческих научно-исследовательских инкубаторов, г. Томск, 2–5 мая 2023 г.)
The results of the research of the gain for a series of silicon photomultipliers are presented. A model for research the characteristics of photodetectors in a temperature chamber was assembled. The amplification factors of the samples were determined at voltages 38 – 42 V and temperatures from –20 to +40 °C. The recommended operating conditions for photodetector samples were revealed.